Monoclonal anti-TNFα antibody (infliximab) in the treatment of patient with thyroid associated ophthalmopathy - Komorowski, Jan; Jankiewicz-Wika, Joanna; Siejka, Agnieszka; Ławnicka, Hanna; Kłysik, Anna; Goś, Roman; Majos, Agata; Stefańczyk, Ludomir; Stępień, Henryk (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
TNFα (tumor necrosis factor alpha) plays a central role in the development of thyroid associated ophthalmopathy (TAO). We describe and document by ophthalmic (CAS and NO SPECS scales) and radiological (MRI) evaluation a positive effect of anti-TNFα antibody (infliximab) administration on active TAO in a 58 years old woman with Graves’ disease. The single dose of infliximab administration resulted in a dramatic reduction of inflammation studies and improvement of visual function as measured by MRI and CAS and NO SPECS scales, without noticeable short-term side effects. A randomized prospective study is needed to determine whether infliximab proves to be sufficiently effective in reducing the inflammatory symptoms of TAO, and whether it can be administered safely for a prolonged period without side effects.